(untitled) (Balthazar, 2021)
This paper examines the intersection of Freudian and Lacanian psychoanalysis with Queer Theory. Starting from an analysis of the Freudian reception in the Second-wave Feminism (1960-1980), the current revival of the anti-psychoanalytic debate is focused, with particular reference to the thought of the transgender philosopher Paul B. Preciado. The aim is to reveal how psychoanalysis turns out to be a valid ally of feminism from an epistemological point of view, and - more radically - how a new ’psychoanalytic feminism’ can be configured. An investigation into the condition of women in contemporary times cannot but pass from the formations of the unconscious, from the Symbolic and from the structuring of Desire, towards a psychoanalysis recoinceived as a crossroad of political implications and transfeminist processes of subjectification.